Pharmacological inhibition of apical sodium‐dependent bile acid transporter changes bile composition and blocks progression of sclerosing cholangitis in multidrug resistance 2 knockout mice. Issue 2 (21st August 2015) - Miethke, Alexander G.; Zhang, Wujuan; Simmons, Julia; Taylor, Amy E.; Shi, Tiffany; Shanmukhappa, Shiva Kumar; Karns, Rebekah; White, Shana; Jegga, Anil G.; Lages, Celine S.; Nkinin, Stephenson; Keller, Bradley T.; et al.
Abstract : Deficiency of multidrug resistance 2 (mdr2), a canalicular phospholipid floppase, leads to excretion of low‐phospholipid "toxic" bile causing progressive cholestasis. We hypothesize that pharmacological inhibition of the ileal, apical sodium‐dependent bile acid transporter (ASBT), blocks progression of sclerosing cholangitis in mdr2 –/– mice. Thirty‐day‐old, female mdr2 –/– mice were fed high‐fat chow containing 0.006% SC‐435, a minimally absorbed, potent inhibitor of ASBT, providing, on average, 11 mg/kg/day of compound. Bile acids (BAs) and phospholipids were measured by mass spectrometry. Compared with untreated mdr2 –/– mice, SC‐435 treatment for 14 days increased fecal BA excretion by 8‐fold, lowered total BA concentration in liver by 65%, reduced total BA and individual hydrophobic BA concentrations in serum by >98%, and decreased plasma alanine aminotransferase, total bilirubin, and serum alkaline phosphatase levels by 86%, 93%, and 55%, respectively. Liver histology of sclerosing cholangitis improved, and extent of fibrosis decreased concomitant with reduction of hepatic profibrogenic gene expression. Biliary BA concentrations significantly decreased and phospholipids remained low and unchanged with treatment. The phosphatidylcholine (PC)/BA ratio in treated mice corrected toward a ratio of 0.28 found in wild‐type mice, indicating decreased bile toxicity. Hepatic RNA sequencing studies revealed up‐regulation of putative anti‐inflammatory and antifibrogenic genes, including Ppara and Igf1, and down‐regulation of several proinflammatory genes, including Ccl2 and Lcn2, implicated in leukocyte recruitment. Flow cytometric analysis revealed significant reduction of frequencies of hepatic CD11b + F4/80 + Kupffer cells and CD11b + Gr1 + neutrophils, accompanied by expansion of anti‐inflammatory Ly6C – monocytes in treated mdr2 –/– mice. Conclusion : Inhibition of ASBT reduces BA pool size and retention of hydrophobic BA, favorably alters the biliary PC/BA ratio, profoundly changes the hepatic transcriptome, attenuates recruitment of leukocytes, and abrogates progression of murine sclerosing cholangitis. (Hepatology 2016;63:512–523)